2002
DOI: 10.1113/jphysiol.2001.013015
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect modulation of rat cardiac sarcoplasmic reticulum function by n–3 polyunsaturated fatty acids

Abstract: Measurements were made of trans‐sarcolemmal Ca2+ fluxes and intracellular [Ca2+]i in rat ventricular myocytes loaded with Indo‐1 to determine how the n‐3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) suppresses spontaneous waves of Ca2+ release. We report that in 10 μm EPA, the Ca2+ efflux generated by individual waves increased by 11.3 ± 4.9 % over control levels. However, wave‐generated efflux per unit time fell overall by 19 ± 5.3 %. On removal of EPA, wave frequency increased transiently such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Additionally, EPA decreased diastolic Ca 2+ concentrations and imaging of Ca 2+ waves showed that EPA also increased Ca 2+ wave amplitudes and propagation [55]. Increased Ca 2+ wave amplitudes by EPA correlated with enhanced sarcoplasmic reticulum load in rat ventricular myocytes [55][56][57]. It was concluded that ω3-PUFAs reduce sarcoplasmic reticulum Ca 2+ uptake and also inhibit Ca 2 + -release (ryanodine receptors (RyR).…”
Section: Calcium Homeostasis and Sarcoplasmic Reticulum Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, EPA decreased diastolic Ca 2+ concentrations and imaging of Ca 2+ waves showed that EPA also increased Ca 2+ wave amplitudes and propagation [55]. Increased Ca 2+ wave amplitudes by EPA correlated with enhanced sarcoplasmic reticulum load in rat ventricular myocytes [55][56][57]. It was concluded that ω3-PUFAs reduce sarcoplasmic reticulum Ca 2+ uptake and also inhibit Ca 2 + -release (ryanodine receptors (RyR).…”
Section: Calcium Homeostasis and Sarcoplasmic Reticulum Functionmentioning
confidence: 95%
“…Acute administration of ω3-PUFAs leads to a decrease in diastolic Ca 2+ concentration in rat ventricular myocytes and in ventricular myocytes isolated from rabbits with heart failure [28,55,57]. Furthermore, EPA reduces spontaneous waves of Ca 2+ -release from the sarcoplasmic reticulum that underlie DAD-related arrhythmias [28,12].…”
Section: Calcium Homeostasis and Sarcoplasmic Reticulum Functionmentioning
confidence: 99%
“…10,13 Reductions in intracellular calcium by 3-PUFAs may be due to block of I Ca,L 10 and/or inhibition of the calcium release channels of the SR, the ryanodine receptors in the SR membrane. 12,13,29 Indeed, acute administration of 3-PUFAs reduced the open probability of the ryanodine receptors in the SR membrane in isolated SR vesicles. 29,30 In our study, similar mechanisms may account for the reduction in diastolic and systolic calcium levels induced by 3-PUFAs.…”
Section: Cytoplasmic Calciummentioning
confidence: 99%
“…However, acute application of 3-PUFAs increased SR calcium content in healthy rat myocytes. 12,13 Further experiments are needed to establish the effect of fish oils on SR calcium content in HF.…”
Section: Cytoplasmic Calciummentioning
confidence: 99%
See 1 more Smart Citation